2022
DOI: 10.31234/osf.io/wj57x
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A metacognitive approach to the study of motion-induced duration biases reveals inter-individual differences in forming confidence judgements

Abstract: Our ability to estimate the duration of sub-second visual events is prone to distortions, which depend both on sensory and decisional factors. To disambiguate between these two influences, we can look at the alignment between discrimination estimates of duration at the point of subjective equality and confidence estimates when the confidence about decisions is minimal, because observers should be maximally uncertain when two stimuli are perceptually the same. Here, we used this approach to investigate the rela… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 49 publications
(77 reference statements)
0
3
0
Order By: Relevance
“…To make an analogy, in our study HC subjects might be considered as individuals with a promotion focus and LC subjects as prevention focus, and this difference in their strategic tendencies causes a fundamental difference in their confidence level and subsequently the perceived time. This finding can be discussed by a very recent study that found a distinct pattern of inter-individual variations between individuals who used only perceptual differences to score their confidence and people who additionally used information that had no bearing on their discriminating judgments 30 . It is also possible to emphasize that our data imply that HC subjects made all decisions in goods space, and in value comparisons HC subjects valued more gain trials than other conditions 55,56 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To make an analogy, in our study HC subjects might be considered as individuals with a promotion focus and LC subjects as prevention focus, and this difference in their strategic tendencies causes a fundamental difference in their confidence level and subsequently the perceived time. This finding can be discussed by a very recent study that found a distinct pattern of inter-individual variations between individuals who used only perceptual differences to score their confidence and people who additionally used information that had no bearing on their discriminating judgments 30 . It is also possible to emphasize that our data imply that HC subjects made all decisions in goods space, and in value comparisons HC subjects valued more gain trials than other conditions 55,56 .…”
Section: Discussionmentioning
confidence: 99%
“…Given the importance of confidence in decision making, however, the relationship between confidence and time perception is lacking in the literature 30,31 . The current study investigated whether differences in confidence determine how subjects perceive time in a monetary context.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, adaptation to visual motion or flicker biases perceived duration even in the absence of any change in the perceived onset and offset of the test intervals (Gulhan & Ayhan, 2019;Johnston et al, 2006), implying that the content of an interval is taken into account when duration is processed, as hypothesized by some models of duration perception (Johnston, 2010(Johnston, , 2014Roseboom et al, 2019). The observation that intervals with equal length containing stimuli moving at different speed, or with different speed temporal profiles, are perceived to have different durations (Binetti et al, 2012;Bruno et al, 2015;Bruno et al, 2022;Kanai et al, 2006) also points to a central role of interval content in duration perception. Comparing the actual and subjective durations of intervals containing sinusoidal gratings drifting at a constant speed with that of intervals containing accelerating gratings with the same average speed, in an fMRI study, Binetti et al observed two separate subsets of activated areas, one including early visual areas for objective durations and one including more anterior areas and the cerebellum for subjective durations (Binetti et al, 2020).…”
Section: Discussionmentioning
confidence: 99%